A comparison between conventional Pseudomonas aeruginosa rhamnolipids and Escherichia coli transmembrane proteins for oil recovery enhancing. (August 2016) - Alvarez Yela, Astrid Catalina; Tibaquirá Martínez, Maria Alejandra; Rangel Piñeros, Guillermo Andrés; López, Viviana Clavijo; Villamizar, Santiago Hernández; Núñez Vélez, Vanessa Lucía; Abraham, Wolf-Rainer; Vives Flórez, Martha Josefina; González Barrios, Andrés Fernando
Abstract: Biosurfactants have emerged as a remarkable strategy for microbial enhanced oil recovery (MEOR) due to their amphipatic nature, superficial activity and low toxicity. On one hand, conventional biosurfactants for MEOR belong to the rhamnolipids group, which are surface-active compounds of glycolipid-type. On the other hand, transmembrane proteins have been studied in recent years and have shown good surface tension reduction potential. This work aimed to evaluate and compare the emulsification index (EI), oil displacement ability (ODA) and additional oil recovery (AOR) percentages of rhamnolipids produced by a native isolate Pseudomonas aeruginosa strain Pa4 and OmpA produced by Escherichia coli . The results confirmed a high recovery potential for both of the biosurfactants with the best superficial activity for P. aeruginosa rhamnolipid mixture (EI of 95% and ODA of 59.94 cm 2 ) and the highest recovery for OmpA, obtaining an AOR of 12%. Highlights: We compared rhamnolipids and transmembrane proteins for enhanced oil recovery. Rhamnolipids showed a higher ODA and IE than OmpA. OmpA had the best performance related to AOR. These biosurfactants have a different effect in the recovery process and outstanding activity for enhancing oil recovery.